Konstytucyjne przesłanki ograniczenia wolności i praw człowieka ze względu na ochronę zdrowia publicznego w świetle doświadczeń zwalczania COVID-19 - Bernaciński, Łukasz (Ograniczenia praw i wolności wprowadzone w Polsce w związku z epidemią COVID-19: Aspekty prawne, medyczne oraz ekonomiczne, 2022)
Restrictions on human rights and freedoms enacted in connection with the fight against COVID-19 reminded the public that the Constitution is not a symbolic act, but a document laying the foundations for the functioning of the state and a guarantee of the inviolability of human freedoms and rights. Due to the fact that the fight against COVID-19 was based on the limitation of the freedoms and rights of individuals, it should be recalled which constitutional conditions should be met by such restrictions enacted for the protection of public health. Article 31 (3) of the Polish Constitution sets out for state authorities the conditions and limits of interference in the sphere of freedoms and rights of individuals. The former include the requirement of the statutory form of introducing restrictions, which enforces the transparency of the legislative process and ensures that the content of the regulation is controlled by the representatives of the nation sitting in the parliament. Moreover, enacting restrictions must be related to the protection of one of the values listed in the provision, including public health. The limits of interference are determined by the principle of proportionality and the prohibition of violating the essence of freedoms and rights. The legislative activity of the COVID-19 epidemic has shown that the enacted law raises constitutional doubts at the level of a formal premise. Enacting restrictions on freedoms and rights in sub-statutory acts based on a questionable legal basis has led to social unrest, undermined citizens’ trust in the state and the laws it enacted, and weakened the actual impact of legal regulations. The latter should be assessed negatively from the point of view of the usefulness imperative. The implementation of the requirement of proportionality in the strict sense may also raise a number of doubts. Finally, the practice of suspending the constitutional rights of an individual can be assessed negatively. An example of such a practice may be a temporary, total ban on certain types of economic activity or severe restrictions on the number of believers who can participate in religious worship.